Magnetic and optical behaviors of SnO2-x thin films with oxygen vacancies prepared by atomic layer deposition. Issue 3 (15th February 2019) - Liu, Shoufa; Qiao, Xun; Wang, Yinwei; Xie, Huan; Zhang, Ning; Liu, Dancheng
Abstract: SnO2-x thin films with different concentration oxygen vacancies were prepared by Atomic Layer Deposition (ALD). Specifically, the oxygen vacancy concentration was controlled by the oxidation pulse time during the ALD process. The crystal structure of the as-prepared thin films was determined by XRD, and the magnetic properties were measured by VSM, while the optical properties were measured by optical transmittance spectrum. The results showed that the oxygen vacancy concentration of the SnO2-x could be controlled by the oxidation pulse time, and the crystal structures, magnetic properties, and optical properties were largely impacted by the concentration of oxygen vacancy.